SWOT and CSF Analysis of the Ground Fish Business at Alang - alang Lebar Market Palembang - Siska Almaniar; Tika Handayani; Triayu Rahmadiah; Arabiatul Adwiyah; Ayu Kalista; Junainah Junainah; Septi Hermialingga (International Journal of Economics and Management Sciences, 2025)
The city of Palembang, traversed by the Musi River, is well suited for industrial development in the fisheries sector. The area is renowned for its distinctive regional cuisine, one of which is pempek which is a processed fish product. Entrepreneurs supporting the supply of raw materials for processed fish products include ground fish businesses. The ground fish industry continues to expand, with business owners striving to maintain and enhance product quality and service standards to remain competitive and promote growth. In this regard, the decisions made by leaders significantly impact an organization’s ability to achieve its objectives. Therefore, appropriate methodologies are required to analyze the key factors influencing success or failure. SWOT analysis helps identify external opportunities and threats as well as internal strengths and weaknesses. Additionally, CSF analysis provides a clearer interpretation of key elements, defines essential activities, and supplies relevant information. Furthermore, this research proposes strategies to enhance efficiency, effectiveness, and value at every stage of the value chain. It is expected that this analysis will assist businesses in optimizing resources and improving the competitiveness of ground fish enterprises in the market. This study aims to provide a comprehensive analysis of strategic measures that can enhance the competitive advantage of ground fish businesses in the fisheries and food processing sectors.